2012
DOI: 10.1002/ece3.406
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow at major transitional areas in sea bass (Dicentrarchus labrax) and the possible emergence of a hybrid swarm

Abstract: The population genetic structure of sea bass (Dicentrarchus labrax) along a transect from the Atlantic Ocean (AO) to the Eastern Mediterranean (EM) Sea differs from that of most other marine taxa in this area. Three populations (AO, Western Mediterranean [WM], EM) are recognized today, which were originally two allopatric populations. How two ancestral genetic units have evolved into three distinct units has not been addressed yet. Therefore, to investigate mechanisms that lead to the emergence of the central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 118 publications
(220 reference statements)
3
37
0
Order By: Relevance
“…Wild sea bass used to produce the broodstock for this study was collected from five distinct origins in the Northeastern Atlantic or the Mediterranean Sea recognized as the main subpopulations of wild sea bass (Chatain & Chavanne, 2009; Quéré et al., 2012) (Table 1). Former population genetics studies reported that the English Channel and the Bay of Biscay belong to the same panmictic unit in sea bass (Naciri et al., 1999; Lemaire et al., 2005; Fritsch et al., 2007; Coscia et al., 2012; Souche et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Wild sea bass used to produce the broodstock for this study was collected from five distinct origins in the Northeastern Atlantic or the Mediterranean Sea recognized as the main subpopulations of wild sea bass (Chatain & Chavanne, 2009; Quéré et al., 2012) (Table 1). Former population genetics studies reported that the English Channel and the Bay of Biscay belong to the same panmictic unit in sea bass (Naciri et al., 1999; Lemaire et al., 2005; Fritsch et al., 2007; Coscia et al., 2012; Souche et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Panmixia justified to not include further population subdivision (as dam and/or sire) to the data set. The sea bass population from the Gulf of Lions was also found to be panmictic (Garcia de León, Chikhi, & Bonhomme, 1997; Quéré et al., 2012), and, as for NAT, no further population subdivision as sire or dam was included in the analyses. The distinction between NAT and SAT is motivated by findings by Castilho and McAndrew (1998) and Souche et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations